Molecular and cytogenetic studies of 101 infertile men with microdeletions of Y chromosome in 1,306 infertile Korean men - Kim, Min Jee (Springer US, 2012)
OBJECTIVES: To determine the prevalence of Y chromosome microdeletions in infertile Korean men with abnormal sperm counts and to assess the clinical features and frequency of chromosomal abnormalities in Korean patients with microdeletions. METHODS: A total of 1,306 infertile men were screened for Y chromosome microdeletions, and 101 of them had microdeletions. These 101 men were then retrospectively studied for cytogenetic evaluation, testicular biopsy and outcomes of IVF and ICSI. RESULTS: The overall prevalence of Y chromosome microdeletions in infertile men was 7.7 % (101/1,306). Most microdeletions were in the AZFc region (87.1 %), including deletions of AZFbc (24.7 %) and AZFabc (8.9 %). All patients with AZFa, AZFbc and AZFabc deletions had azoospermia, whereas patients with an AZFc deletion usually had low levels of sperm in the ejaculate or in the testis tissues. Chromosomal studies were performed in 99 men with microdeletions, 36 (36.4 %) of whom had chromosomal abnormalities. Among the infertile men with Y chromosome microdeletions in this study, the incidence of chromosomal abnormality was 48.6 % in the azoospermic group and 3.7 % in the oligozoospermic group. Among the 69 patients with microdeletions and available histological results, 100.0 % of the azoospermic group and 85.7 % of the oligozoospermic group had histological abnormalities. The frequency of both chromosomal abnormalities and histological abnormalities was higher in the azoospermic group compared to the oligozoospermic group. Thirty-four ICSI cycles with either testicular (n = 14) or ejaculated spermatozoa (n = 20) were performed in 23 couples with men with AZFc microdeletion. Thirteen clinical pregnancies (39.4 %) were obtained, leading to the birth of 13 babies. CONCLUSIONS: The study results revealed a close relationship between microdeletions and spermatogenesis, although IVF outcome was not significantly affected by the presence of the AZFc microdeletion. Nevertheless, Y chromosome microdeletions have the potential risk of being transmitted from infertile fathers to their offspring by ICSI. Therefore, before using ICSI in infertile patients with severe spermatogenic defects, careful evaluations of chromosomal abnormalities and Y chromosome microdeletions screening should be performed and genetic counseling should be provided before IVF-ET.